Elevated Intraocular Pressure after Pars Plana Vitrectomy: A Review - Yadgari, Maryam; Shahriari , Mansoor; Farsi, Pirouzeh (Journal of Ophthalmic and Optometric Sciences, 2019)
Intraocular pressure (IOP) elevation is a well-known complication after pars plana vitrectomy with or without tamponade. The mechanism of increase in IOP can be open angle, closed angle or both. Oxidative stress is hypothesized to have a significant role in the pathogenesis of post vitrectomy elevated IOP and the presence of the lens probably has a protective role. The use of silicone oil and intraocular gases as tamponade is related to higher risk of post-operative elevated IOP and causes longer-term IOP elevation. Anti-inflammatory agents, mydriatics, anti-glaucoma medications especially aqueous suppressants, glaucoma surgery and laser procedures might be used for controlling post vitrectomy elevated IOP. Glaucoma shunt implantation and cyclodestructive procedures are the most important surgeries performed for treatment of uncontrolled intraocular pressure after vitrectomy.